A Full Rank Condition for Continuous-Time Optimization Problems with Equality and Inequality Constraints - Monte, Moisés Rodrigues Cirilo; de Oliveira, Valeriano Antunes (Trends in Computational and Applied Mathematics, 2019)
First and second order necessary optimality conditions of Karush-Kuhn-Tucker type are established for continuous-time optimization problems with equality and inequality constraints. A full rank type regularity condition along with an uniform implicit function theorem are used in order to achieve such necessary conditions.